PADASAN AND SYMBOLS OF PUBLIC SELF-HEALTH IN JAVANESE-ISLAMIC CULTURAL PERSPECTIVE - Hidayatullah, Ahmad Fauzan (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
The purpose of this research is to increase the desire for healthy livingbehavior of the community, especially thorough hand washing, as well asprovide insights to the community to always preserve the healthy livingculture that has existed in the culture of Javanese society and Islam. Thisresearch uses a method through literature studies with literature review. Theresults showed that the padasan has been known since time immemorial.On the site of Ki Buyut Trusmi, the padasan is placed to enter a holierplace. Padasan in Al-Aqsa mosque Kudus have Buddhist architecturestyle. In the new normal era, the government encourages the public to getused to washing their hands with soap. This research concludes the habit ofwashing hands has been done by the previous community but using atraditional tool called padasan.